In Situ Exsolved Ni-Decorated Ba(Ce(0.9)Y(0.1))(0.8)Ni(0.2)O(3−δ) Perovskite as Carbon-Resistant Composite Anode for Hydrocarbon-Fueled Solid Oxide Fuel Cells - Liu, Yanya (ACS Omega, 2019)
[Image: see text] In this study, in situ exsolved Ni–Ba(Ce(0.9)Y(0.1))(0.8)Ni(0.2)O(3−δ)+Gd(0.1)Ce(0.9)O(1.9) (Ni–BCYN+GDC) perovskite anode is studied for application in hydrocarbon-fueled solid oxide fuel cell (SOFC). The electrocatalytic activities of the oxidation reaction of anode in hydrogen and methane atmospheres are studied. The results show that the surface-exsolved Ni nanoparticles can significantly improve the electrochemical properties of the anode. The polarization resistances of the studied anode in hydrogen and methane atmospheres at 750 °C are as low as 0.0042 and 0.0054 Ω·cm(–2), respectively. At the same time, a 36 h short-term open-circuit voltage test under a methane atmosphere confirms that the Ni–BCYN+GDC composite anode exhibits a good carbon deposition resistance. These results demonstrate that the Ni–BCYN+GDC composite anode is a potential novel anode material candidate for hydrocarbon-fueled SOFC.